2021
DOI: 10.3390/diagnostics11050798
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Genotype and Perinatal Period, Time of Diagnosis and Anthropometric Data before Commencement of Recombinant Human Growth Hormone Treatment in Polish Patients with Prader–Willi Syndrome

Abstract: Genotype–phenotype correlation in patients with Prader–Willi syndrome (PWS) has still not been fully described. We retrospectively analysed data of 147 patients and compared groups according to genetic diagnosis: paternal deletion of chromosome 15q11-q13 (DEL 15, n = 81), maternal uniparental disomy (UPD 15, n = 10), excluded DEL 15 (UPD 15 or imprinting centre defect, UPD/ID, n = 30). Group DEL 15 had an earlier genetic diagnosis and recombinant human growth hormone (rhGH) start (p = 0.00), with a higher insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
3
5
1
Order By: Relevance
“…Notably, birth weight SDS was significantly lower in PWS, while head circumference SDS at birth was not affected. The higher prevalence of SGA birth in the mUPD group has not been reported earlier, although one study found a tendency towards a lower birth weight SDS in the mUPD group [22]. In an Italian cohort of PWS newborns, no difference in birth weight was found between genotypes, but females with a deletion had a smaller birth length compared to the mUPD subtype [20], but we could not confirm this.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Notably, birth weight SDS was significantly lower in PWS, while head circumference SDS at birth was not affected. The higher prevalence of SGA birth in the mUPD group has not been reported earlier, although one study found a tendency towards a lower birth weight SDS in the mUPD group [22]. In an Italian cohort of PWS newborns, no difference in birth weight was found between genotypes, but females with a deletion had a smaller birth length compared to the mUPD subtype [20], but we could not confirm this.…”
Section: Discussioncontrasting
confidence: 88%
“…Although perinatal and neonatal characteristics in PWS have been reported [6,[18][19][20][21][22], the spectrum of clinical features which characterizes PWS in early life is still relatively unclear or inappropriate molecular testing was performed [21]. In addition, a comparison with healthy infants is, to our knowledge, not yet described.…”
Section: Introductionmentioning
confidence: 97%
“…Analysis of the genetic background of the study population confirmed our previous research conclusions that a UPD/ID genetic background seems to be recognised later in life and therefore these patients start rhGH therapy at an older age [ 35 ]. Moreover, as expected, the earliest genetic diagnosis leads to the earliest rhGH commencement.…”
Section: Discussionsupporting
confidence: 77%
“…The rhGH treatment was accepted by the Polish Coordination Group for rhGH Treatment. We recently published the first part of the data analysis regarding perinatal characteristics, anthropometric data and biochemical data before commencement of rhGH treatment in relation to the genetic subtype and the age of genetic diagnosis [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation